Apostary in the New Testament communities - Oropeza, B. J.; (1961-...) (U.S.A, 2012)
B. J. Oropeza offers the most thorough examination in recent times on the subject of apostasy in the New Testament. The study examines each book of the New Testament with a fourfold approach that identifies the emerging Christian community in danger, the nature of apostasy that threatens the congregations, and the consequences of defection. Oropeza then compares the various perspectives of the communities in Christ in order to determine the ways in which they perceived apostasy and whether defectors could be restored. In this second volume of a three-volume set titled Apostasy in the New Testament Communities, Oropeza focuses on the Christ communities of the undisputed and disputed Pauline Letters.
Keywords: Church - History - ca 30-600 (Early Church)